Group-analytic Practice Today: Intersubjective Perspectives and the Relational Paradigm. (September 2017) - Potthoff, Peter
Over the past 50 years psychoanalysis and group analysis have quite moved apart from each other with very little exchange and cooperation left, while the pioneers of group analysis (Foulkes, Bion) emphasized the link with psychoanalysis. With the 'intersubjective turn' in psychoanalysis during the 1980s substantial common ground for group analysis and psychoanalysis has emerged, but not been completely recognized and appreciated in both disciplines. The author demonstrates areas of possible overlap and cross-fertilization mainly drawing on concepts from relational psychoanalysis. The idea of the inevitable embeddedness of analyst and analysand in the psychoanalytic process has already been present in Foulkes' writings concerning the role of the conductor, but not very much elaborated. Other relational concepts like dissociation, enactment, mutuality and self-disclosure might be fruitfully integrated into contemporary group-analytic theorizing, too. Conversely, group-analytic perspectives could increase awareness of the importance of context (social, cultural, institutional) also for the dynamics of individual analysis. The understanding of group processes could help to grasp and negotiate more successfully the notorious difficulties in psychoanalytic institutions. To illustrate theory the author presents detailed material from a group session.